Specifics in status of adults after correction of congenital heart disease in childhood - O. Rusyn (Ukrainian Journal of Cardiovascular Surgery, 2016)
The Objective of the work – revealing the condition peculiarities of adults after correction of congenital heart disease on the bases of Transcarpathian regionDuring 2014–2016 449 patients from Transcarpathian Region at the age of 18 and 73 and older, who underwent surgery on different types of congenital heart defects in 1990–2013, were examined on the bases of Transcarpathian Regional Clinical Cardiology Clinic. Average period of remote monitoring of the patients is about 12 years and a half but no more than 6 additional.On the bases of the history of the disease, objective examination and echocardiography data the patients who underwent surgery were identified a number of pathologies, which directly or indirectly were connected with congenital heart defects and comorbidities.These patients require lifelong medical support of multi-disciplinary team of specialists (cardiologists, cardiovascular surgeons, psychologists, therapists, ultrasound therapists, ect.) for providing highly qualified medical care, determination of indications for second surgery and reoperation in optimal terms.